2010
DOI: 10.1016/j.rser.2010.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ESCO activities using country indicators

Abstract: Energy Service Companies (ESCOs) are private sector instruments that offer energy-/emission-improvement (energy saving, energy efficiency, energy conservation, emission reduction) projects in the developed and in some developing countries. Literature reveals that energy-/emission-improvements of countries may be related to their innovation-and R&D-activity levels. In this work, we use a literature data on the activities and the sectors targeted by ESCOs in 38 countries, summarized in terms of the age of ESCO m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 15 publications
(10 reference statements)
0
28
0
Order By: Relevance
“…Some of these services can be O&M, sales, demand-side management, energy audits, and assisting customers [41]. In emerging markets, this model delivers sustainable energy solutions while creating jobs [42,43]. Generally, this scheme facilitates the implementation of small networks throughout communities, provides a cost-effective electricity service, and improves the living conditions of inhabitants [43].…”
Section: Management Modelsmentioning
confidence: 99%
“…Some of these services can be O&M, sales, demand-side management, energy audits, and assisting customers [41]. In emerging markets, this model delivers sustainable energy solutions while creating jobs [42,43]. Generally, this scheme facilitates the implementation of small networks throughout communities, provides a cost-effective electricity service, and improves the living conditions of inhabitants [43].…”
Section: Management Modelsmentioning
confidence: 99%
“…Previous studies found that the selection of EPC models depend on a number of factors, including maturity of local financial market, creditability of contracting parties, expected energy savings, as well as confidence on energy efficiency technologies [3]. Okay and Akman [38] indicated that the shared saving model is preferred in developing countries because the host has no financial risk, with the benefit that the debt does not appear on the host's balance sheet. Larsen et al [39] discussed that the guaranteed saving model is more preferable in the public sector in the U.S. due to the greater certainty of savings since the ESCO fully bears the performance risk of proposed ECMs.…”
Section: Mode Of Epc Projectmentioning
confidence: 99%
“…The project is funded by government, third party supplier or financier. Countries in which this EPC model is employed include India, China, and Brazil [35][36].…”
Section: A Shared Savings Contractmentioning
confidence: 99%